Continuous Scanning Technique with Barkhausen Magnetic Noise for Carbon Steel Sheets - Leosdan Figueredo Noris; Linilson Rodrigues Padovese; Sérgio Souto Maior Tavares; Juan Manuel Pardal (Materials Research, 2019)
This work studies the application of a Non-Destructive Inspection Technique (NDIT), based on the Magnetic Barkhausen Noise (MBN), for the detection of non-homogeneous regions in carbon steel plates. It presents the advances in the development of a variant of a new non-destructive magnetic test technique, called Continuous Scanning Magnetic Barkhausen Noise (CSMBN). The non-homogeneous or damaged regions were produced by plastic deformations in rolled and annealed sheets of SAE 1060 and 1070 steels. MBN is generated by abrupt changes in the magnetization of materials when subjected to alteration. The sensitivity of the MBN signals in the detection of plastic deformations was analyzed varying parameters such as excitation magnetic field frequency and the speed of movement of the probe. The behavior of the root mean square of magnetic Barkhausen Noise signal (RMSMBN) parameter was correlated with the position of the nonhomogeneous regions detected in the samples. An evaluation of the technique applied to the measurement was made, comparing the results obtained with the Static Magnetic Barkhausen Noise (SMBN) technique, which is a method already established in the literature. The results showed that in all cases studied it was possible to detect the position of the damage, due to variation of the magnetic field. These changes are affected by the presence and distribution of elastic stresses (compression and traction), plastic deformation and microstructure modification. The results of CSMBN were similar to the SBMN with the advantage of being a continuous and more productive procedure. This new technique increases the spectrum of NDIT solutions for problems not contemplated by existing techniques.